PERAN KONTEN INSTAGRAM DALAM MEMEDIASI PENGARUH CITRA MEREK TERHADAP MINAT BELI PADA BRAND GEOFF MAX - Shafira Ferdianti; Akhmad Yunani (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Content is a crucial factor in marketing communications through social media. Content can shape brand image and ultimately consumer buying interest. This study aims to determine the role of Instagram content in mediating the effect of brand image on purchase intention at the Geoff Max brand. By involving a sample of four hundred Geoff Max Instagram followers, this research examines the role of brand image in mediating the effect of Instagram content on Geoff Max's consumer buying interest. Tests carried out with path analysis show that Instagram content has a significant effect on brand image. Besides that, brand image has a significant effect on Geoff Max's consumer buying interest. The Sobel test shows that brand image significantly mediates the effect of Instagram content on Geoff Max's consumer buying interest.